Volume replacement with diced acellular dermal matrix in oncoplastic breast-conserving surgery: a prospective single-center experience - Hongki Gwak; Ye-Won Jeon; Seung-Taek Lim; Seon-Young Park; Young-Jin Suh (World Journal of Surgical Oncology, 2020)
Abstract Background Several studies have reported the use of acellular dermal matrix in breast reconstruction. However, the primary role of acellular dermal matrix in these studies was to support the implant; there are no reports on the use of acellular dermal matrix exclusively as volume replacement. Thus, we aimed to evaluate the safety and effectiveness of filling of the defect with acellular dermal matrix in oncoplastic breast-conserving surgery. Methods We prospectively recruited 120 adult breast cancer patients who were scheduled to undergo oncoplastic breast-conserving surgery with acellular dermal matrix filling from 2017 to 2018. Intraoperatively, diced human acellular dermal matrix measuring 3–5 mm was used on each side to fill in the excisional defect immediately. After 6 months, satisfaction of the patients and surgeons with overall and cosmetic outcomes was evaluated with a survey using a 10-point scale. Postoperative complications were assessed at 2 weeks and 6 months postoperatively. Results Of the 117 patients who were evaluated for their satisfaction, 94.0% were strongly satisfied with the cosmetic outcomes and 90.4% were strongly satisfied overall. Patient overall satisfaction scores were higher than surgeon satisfaction scores (p < 0.001). Of the 117 patients who underwent evaluation of complications 6 months postoperatively, six (5.1%) had hematoma and seven (6.0%) had seroma. The overall reoperation rate due to complications was 8.5%. Only two patients needed acellular dermal matrix removal due to hematoma and inflammation. Conclusion Oncoplastic breast-conserving surgery with acellular dermal matrix filling of defects can be performed safely with high cosmetic satisfaction. Trial registration ICTRP, KCT0003886; retrospectively registered May 3, 2019, http://apps.who.int/trialsearch/Trial2.aspx?TrialID=KCT0003886